Strategies for adaptation of Russian commercial banks to innovative technologies - Solenaya, O. S. (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The article discusses the strategies of the bank in the innovation sphere, which are important components of general development strategies, their content and the order of choice in the context of digitalization of the economy and global changes in the world banking system. It is shown that the main feature of banking innovations is the priority of innovations in the field of technology, associated with the relative substantive immutability of banking services. The dependence of the success of the strategy of adaptation of banks to technological innovations on the quality of the analysis of the external environment of their functioning in comparison with their own capabilities and the correctness of forecasting innovation processes is determined. Materials and methods. The study was conducted on the principles of consistency, based on the unity of the approach to the formation of the strategy of commercial banks in the innovation sphere, as a component of their long-term activities in the context of digitalization and the new content of globalization processes in the direction of sustainable and effective development. It is based on the analysis of modern scientific publications, official data on the development of banks and the banking system in Russia, the conclusions of economists on the essence of innovations in the development of financial and credit organizations, the use of existing approaches to summarizing and presenting data, general scientific methods for studying processes and phenomena. Results and discussion. The entire bank system and its components interact with the external environment that promotes or hinders innovation. The innovation climate must be analyzed from the standpoint of the nature and degree of influence on the bank's innovation strategy, the most important component of which is innovative technologies, from the standpoint of the direct influence on the effectiveness of its work. The bank's strategy in the innovation sphere is not a detailed plan of innovation activities, which is an important component of its overall development strategy. The success of the strategy of adaptation of banks to technological innovations depends on the quality of the analysis of the external environment of their functioning in comparison with their own capabilities and the correctness of forecasting innovation processes, as shown in this study. Conclusion. In recent years, banking innovations have almost always been associated with digital technologies and artificial intelligence, the time of their implementation is constantly decreasing, and diffusion into the sphere of banking activities is accelerating. The process of dissemination of banking innovative technologies is influenced by their digital nature and significant advantages in comparison with previously used ones. The limitations are the material costs of purchasing software and the readiness of personnel to use it. In the conditions of high competition in the banking sector, innovations are becoming the main source of income growth for its participants. Banking technological innovations are closely related to the development of infrastructure, sometimes also of an innovative nature. Some banking innovations relate to management systems and banking infrastructure. The development of banking infrastructure in the context of digitalization of the economy and the use of big data tools is mainly aimed at the development and application of cross-channel information systems for integrating the information systems of domestic banks and their connections with foreign ones (where possible). All banking innovations have a significant impact on the current business models of commercial banks, increasing the efficiency of their activities and at the same time the level of competition both in the banking sector and in the financial markets as a whole